Functional, Structural, and Neurotoxicity Biomarkers in Integrative Assessment of Concussions - Dambinova, Svetlana A.; Maroon, Joseph C.; Sufrinko, Alicia M.; Mullins, John David; Alexandrova, Eugenia V.; Potapov, Alexander A. (Frontiers in Neurology, 2016)
Concussion is a complex, heterogenous process affecting the brain. Accurate assessment and diagnosis and appropriate management of concussion are essential to ensure athletes do not prematurely return to play or others to work or active military duty, risking re-injury. To date, clinical diagnosis relies primarily on evaluating subjects for functional impairment using instruments that include neurocognitive testing, subjective symptom report, and neurobehavioral assessments, such as balance and vestibular-ocular reflex testing. Structural biomarkers, defined as advanced neuroimaging techniques and biomarkers assessing neurotoxicity and immunoexcitotoxicity may complement the use of functional biomarkers. We hypothesize that neurotoxicity AMPA, NMDA, and kainite receptor biomarkers might be utilized as a part of comprehensive approach to concussion evaluations, with the goal of increasing diagnostic accuracy and facilitating treatment planning and prognostic assessment.